PENGARUH PENYULUHAN KESEHATAN MENGGUNAKAN POWER POINT DAN PEMUTARAN VIDEO TERHADAP PERUBAHAN MOTIVASI IBU DALAM PENCEGAHAN KANKER SERVIKS DENGAN METODE IVA DI WILAYAH KERJA PUSKESMAS NANGGALO KOTA PADANG - Fizran Fizran; Evi Maria Lestari Silaban (Ensiklopedia of Journal, 2022)
WHO data in 2017, cancer is the main cause of disease worldwide, every year more than 266,000 deaths from cervical cancer. Overcoming this problem requires efforts to solve the problem with a screening method, namely VIA examination. This study aims to determine the effect of counseling on early detection by playing videos and power points for cervical cancer using the IVA (Visual Inspection of Acetic Acid) method on the motivation of mothers in the working area of the Nanggalo Public Health Center, Padang City. This type of research is a pre-experimental design with one group pre-test and post-test design which has been carried out in the work area of the Nanggalo Health Center, Padang City. The population is EFA as many as 2863 people. Samples were taken by purposive sampling with a total sample of 16 people. Collecting data using a questionnaire and then processing the data with the T-Test test. The results showed that the average value of the mother's motivation before being given counseling was 44.31 with a standard deviation of 2.626. The average value of mother's motivation after counseling was 47.94 with a standard deviation of 2.955. The results of statistical tests using T-Test obtained p-value = 0.0005 <0.05 (α). It can be concluded that there is an effect of Health Counseling Using Power Point and Video Playing on Changes in Mother's Motivation in Cervical Cancer Prevention Using the IVA Method in the Nanggalo Health Center Work Area, Padang City in 2020 and it is hoped that health workers will increase information about early detection of cervical cancer using the IVA method, and to the public to increase their understanding of the importance of early detection of cervical cancer so that people are willing to participate in conducting the IVA test.Keywords: Counseling, Motivation, Power Point and Cervical Cancer Video Screening, VIA.